Atuação profissional dos egressos da Faculdade de Arquivologia da Universidade Federal do Pará - RODRIGUES, Joyce da Cruz (2022)
In Brazil, archivists had their legal recognition in the 70s, but both the profession and archivology are still in the process of development and social recognition, especially after the inclusion of the discipline in higher education institutions in the same decade. In 2011 the Archivology course is instituted at the Federal University of Pará, with the objective of qualifying professionals to work in the State, whether in public or private initiative. From this consideration, this research aimed to verify, from the experience of the first graduates of the UFPA Archivology course, the academic preparation and professional performance in the labor market in eight years of activity. The sample universe for obtaining results comprises the graduates of their first four classes from 2015 to 2019 of the UFPA Archivology course. For the comprehension of this study, national historical aspects and the State of Pará participation in the Archivology development process were contemplated. This is a qualitative and quantitative research whose methodological procedures consisted in the survey of bibliographic and documentary sources, as well as the application of a questionnaire to the target audience in order to gather information that shows the opinion of the graduates about the academic formation and professional performance in the labor market in the organs and companies of the Pará State. The results obtained with this research pointed to a disparity between the federal public sector, the state public sector and the private sector and some concern of graduates to their professional future due to the lack of practice in the academy and the flexibility of the requirements to fill the position of responsibility in the archives of state and municipal public agencies.